Cultural Crossvergence and Social Desirability Bias: Ethical Evaluations by Chinese and Canadian Business Students - Dunn, Paul (Journal of business ethics, 2009)
The purpose of this study is to determine whether there are cross-cultural differences between Chinese and Canadian business students with respect to their assessment of the ethicality of various business behaviors. Using a sample of 147 business students, the results indicate cultural crossvergence; the Chinese (72 students) and Canadians (75 students) exhibit different ethical attitudes toward questionable business practices at the individual level but not at the corporate level. A social desirability bias (a tendency to deny socially unacceptable actions and to admit to socially desirable ones) is also found to be a cross-cultural phenomenon, with the Canadians demonstrating a greater bias than the Chinese. Finally, this bias causes respondents to increase their assessment of the un-ethicality of questionable business activities.